If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 5) = 3(3x + -5) + -31 Reorder the terms: 4(5 + 2x) = 3(3x + -5) + -31 (5 * 4 + 2x * 4) = 3(3x + -5) + -31 (20 + 8x) = 3(3x + -5) + -31 Reorder the terms: 20 + 8x = 3(-5 + 3x) + -31 20 + 8x = (-5 * 3 + 3x * 3) + -31 20 + 8x = (-15 + 9x) + -31 Reorder the terms: 20 + 8x = -15 + -31 + 9x Combine like terms: -15 + -31 = -46 20 + 8x = -46 + 9x Solving 20 + 8x = -46 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 20 + 8x + -9x = -46 + 9x + -9x Combine like terms: 8x + -9x = -1x 20 + -1x = -46 + 9x + -9x Combine like terms: 9x + -9x = 0 20 + -1x = -46 + 0 20 + -1x = -46 Add '-20' to each side of the equation. 20 + -20 + -1x = -46 + -20 Combine like terms: 20 + -20 = 0 0 + -1x = -46 + -20 -1x = -46 + -20 Combine like terms: -46 + -20 = -66 -1x = -66 Divide each side by '-1'. x = 66 Simplifying x = 66
| 18/12= | | 7(x+5)=-25+2x | | 6x+5x=90 | | 3n+26+2n+37+4n+15=180 | | (2x+9)(4x-3)=8x^2-12 | | -4x+3=83 | | 3x-7+x=21 | | -4+3=83 | | 3/4=2 | | -32/4= | | 7(y-1)=49+5y | | -3=-2+1x | | 2x-7+5x=49 | | x+7+2x+53=180 | | 12n-9+62-3n+16n+2=180 | | -32/3= | | 6y=12x-12 | | 7x+8+3x-1+4x+5=180 | | -2(3x+5)=x-52 | | 3u^2-7u-6=0 | | 2(a-4)=2a-8 | | 39=-x | | 4(a-6)=6(a+4) | | .3x+13.7=x-7.37 | | 2w+9w=22 | | 2x*4=20 | | -5(a-2)=5 | | 90=24t-0.8t^2 | | 6a+1-a=16 | | 27(x)-4=6-(x) | | x/3-7/9=5/5 | | 3x/5-6=8 |